Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/bjs.11149
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of completion lymph node dissection in sentinel lymph node-positive melanoma

Abstract: Background: The role of completion lymph node dissection (CLND) in patients with sentinel lymph node (SLN)-positive melanoma continues to be debated. This systematic review and meta-analysis evaluated survival and recurrence rate in these patients who underwent CLND, compared with observation.Methods: A comprehensive MEDLINE and Embase database search was performed for cohort studies and RCTs published between January 2000 and June 2017 that assessed the outcomes of CLND compared with observation in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The value of our pooled study consists in scrupulous analysis of a large group of relevant studies and integrating them in such a way as to draw a unified conclusion. Furthermore, search strategy was wider as compared to previously attempted pooling of data [14,15,17,18,23,40].…”
Section: Discussionmentioning
confidence: 99%
“…The value of our pooled study consists in scrupulous analysis of a large group of relevant studies and integrating them in such a way as to draw a unified conclusion. Furthermore, search strategy was wider as compared to previously attempted pooling of data [14,15,17,18,23,40].…”
Section: Discussionmentioning
confidence: 99%
“…Indicators, not governors” (cited from [ 124 ]). Also, multiple meta-analyses of randomized controlled trials show no survival benefit of lymph node dissection compared to observation in melanoma [ 125 , 126 ]. This not only raises serious questions about today’s patient management, but also about our—lack of—understanding tumor biology.…”
Section: Tumor Microenvironment Remodeling and Adhesion Molecule Alterations Are Involved In Melanoma Cell Fate Motility And Migrationmentioning
confidence: 99%
“…Altogether thirteen studies were included in the quantitative pooled analysis, which showed similar survival in CLND group and observation group (risk ratio [RR] for death 0,85, 95% CI 0,71 to 1,02) and similar recurrence rate (RR 0,91, 0,79 to 1,05). [6] Table 1. compares DeCOG-SLT and MSLT-II studies.…”
Section: Fallen Dogma 1: All Sentinel Node Melanoma Metastasis Warrants Completion Lymphadenectomymentioning
confidence: 99%